Islamic Business Ethics in E-Commerce Trading: A Study of Fiqh Muamalah Regarding Contracts and Ownership - Dallah, Dallah (Yayasan Pendidikan Islam Daarut Thufulah, 2025)
Digital commerce through e-commerce has changed the business landscape worldwide, including in Muslim societies. Although e-commerce is easy and efficient, there are still issues of fiqh muamalah, especially regarding ownership and sale transactions. Islamic business transactions are evaluated from the perspective of ethics and sharia compliance as well as technical aspects. Uncertainty, or gharar, can arise because many online transactions do not follow the principles of valid contracts and do not clearly state the ownership of goods. Therefore, it is important to learn how the principles of Islamic business ethics can be applied to e-commerce, especially in terms of ownership and contract relationships. This study aims to see how e-commerce practices are in line with the principles of Islamic business ethics, especially from the perspective of fiqh muamalah on contracts and ownership. In addition, this study also wants to provide suggestions to ensure that digital transactions are in accordance with sharia values. This study uses a qualitative approach with a library research method. Data were collected by analyzing classical and contemporary literature on fiqh muamalah, e-commerce, and case studies of online transactions. A descriptive-analytical approach was used to analyze the principles of contracts and ownership in Islam. The results show that many e-commerce transactions do not meet the requirements for a valid contract such as clarity of object, price, and ijab kabul. In addition, ownership of goods is often not legally transferred when the transaction is made, especially in a dropship system where the seller does not physically own the goods.